Coaching : evoking excellence in others - Flaherty, James (Burlington, MA : Butterworth-Heinemann, 2010)
The book is an insightful, thought-provoking guide that dissects the art and science of coaching. Beginning with theories, concepts and models, the book moves on to consider rigorous methods of practice and self-observation in a relationship of mutual trust, respect and freedom of expression. It will probe you to rethink how you relate to your clients and your staff, how you produce long-term excellent performance in yourself and how you can become more effective in helping others to achieve their goals This third edition includes a new chapter on communication and a new central case study that runs throughout the book to illustrate the impact of the themes and concepts discussed in the book. Coaching, 3rd edition is a rich learning resource guide for new and experienced coaches who want to challenge their methods of partnering with clients. It is also an inspiring guide for training managers and leaders, human resource development managers and general managers who want to develop their teams. New edition of a coaching classic--let James Flaherty guide you through the principles and practice of helping others to achieve their goals. Theoretically rigorous, thought-provoking and practical--dissects the art and science of coaching and offers clear structures for implementing effective self-improvement and personnel development programs. Revised and updated to include new material on the latest approaches, with a new chapter on communication and a new central case study running throughout the book.
1. The foundation of coaching -- 2. Basic principles -- 3. The flow of coaching -- 4. The coaching relationship -- 5. Openings -- 6. Assessment models -- 7. How things really get done -- 8. Enrollment -- 9. Coaching conversations -- 10. Stuck -- 11. Getting in condition for change -- 12. Track two : working with ourselves.
Includes bibliographical references (p. 205-212) and index.
oif 16/09/14
Loan
Keywords: Mentoring in business; Employees -- Training of; Employees -- Coaching of; Employees -- Counseling of; Executive coaching